CHILDREN’S LITERATURE: THE ADULTS AGENDA FOUND IN FLORA ANNIE STEEL’S THE TWO SISTERS FAIRYTALE - BR SIGIRO, KRISNAWATI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: children’s literature, adults agenda, fairytale, The Two Sisters.In writing children’s literature, adults frequently convey the adults agenda to create well-behaved children. One of popular genres of children’s literature is fairytale. Beyond the magical and adventure inside fairytale, the adults agenda exist in this genre. Perry Nodelman, a scholar of children’s literature gives his statement regarding to position of adults in children’s literature. Nodelman explains that actually adults colonize children covertly in children’s literature.This research is focused to find the adults agenda in The Two Sisters fairytale written by Flora Annie Steel. This research is analyzed using qualitative method. In this research, the data are collected by reading The Two Sisters fairytale. Children’s literature theory by Nodelman is the effective theory to analyze the relation of adults and children in children’s literature. Moreover, the adults agenda can be identified using this theory.The result of this research is there are two big adults agendas found in The Two Sisters fairytale. The first agenda is to dictate children to be good in family and society. The second agenda is to show the position of adults, that adults are strong whereas children are weak. The second adults agenda consist of three sub agendas. The second adults agenda also dictate that it is dangerous for children to have their own desire. Besides, children are dictated to depend on adults, and children are convinced they are weak than adults.Fairytale as one genre of children’s literature cannot be separated from the adults agenda. The existence of the agendas is to make the readers good by learning something from it. Adults believe that the agendas in fairytale are created by adults for the kindness of children. It is to create the ideal characteristic of children based on adult’s standard. It means, the agendas from adults to children are to fulfill the desire of adults. The writer suggests to the next study to analyze the other genres of children’s literature. However, there are many theories in critizing children’s literature. It is suggested to apply Deconstruction theory for the next study to crticize the appearances of the main characters in children’s literature who run out from the stereotypes.